Educational Software for Stress Analysis of Idealized Closed Thin Walled Sections - S. Mohamed Ali, J.; Nur Fadhila, Hasna; M. Burhani, Burhani; Mohammed Riyadh, Miah (International Journal of Engineering and Technology, 2018)
Aerospace structures are typically semi-monocoque structures that are made up of thin-walled closed section reinforced with stiffeners. Stress analysis of such closed thin-walled structures which are statically indeterminate is tedious and time consuming. An educational software which can aid students in carrying out stress analysis of such idealized thin-walled closed sections has been developed. The software enables students to select different types of wing torsion box sections with stiffeners, which may be subjected to bending, shear or torsional loads and evaluate the resulting stresses on it. The software allows the student to idealize a selected twin spar unsymmetrical wing section with multiple booms under multiple loads. Results from this software have been validated against the results in the literature. The software has been developed using MATLAB with graphical user interface (GUI) which is very user friendly.Â Â Â